Optical properties of sensitized tin dioxide thin film prepared by using sol-gel spin coating method - Aziz, Madzlan (FKKKSA, 2008)
Undoped tin dioxide (SnO2)thin films were prepared by sol-gel spin coating process using an alcoholic solution of tin chloride dihydrate (SnCl2.2H2O) as the precursor. The tin dioxide doped terbium (Tb3+) and erbium (Er3+) ion thin films were also prepared using sol gel method in order to form SnO2:Tb3+ and SnO2:Er3+ thin films. The concentration of Tb3+ and Er3+ is 5% in relation with the tin content in the sol. The doped and undoped SnO2 films were sensitized with eosin Y. The diameter of particles in the SnO2 film ranges from 20 to 46 nm with spherical morphology. The particle size of SnO2 doped Tb3+ and SnO2 doped Er3+ thin films are bigger than undoped SnO2 thin films. SnO2 thin films have tetragonal structure with prominent peaks corresponding to (110), (101) and (211) crystal lattice planes. The band gap energy is decreased with the addition of dopant (Tb3+ and Er3+ ion) in sensitized SnO2 thin films. The PL emission peaks of SnO2:Tb3+ sensitized with eosin Y corresponding to the characteristic D?Ftransitions between the energy levels of Tb3+ ion. The addition of erbium (Er3+) to the SnO2 sol results in PL emission peaks that are associated with G?Iand H? I transitions in Er3+ ion.